Time-Division Multiuser MIMO with Statistical Feedback. (3rd February 2008) - Wong Wong, Kai-Kit Kai-Kit; Chen Chen, Jia Jia
Abstract : This paper investigates a time-division multiuser multiple-input multiple-output (MIMO) antenna system inK -block flat fading where users are given individual outage rate probability constraints and only one user accesses the channel at any given time slot (or block). Assuming a downlink channel and that the transmitter knows only the statistical information about the channel, our aim is to minimize the overall transmit power for achieving the users' outage constraint by jointly optimizing the power allocation and the time-sharing (i.e., the number of time slots) of the users. This paper first derives the so-called minimum power equation (MPE) to solve for the minimum transmit power required for attaining a given outage rate probability of a single-user MIMO block-fading channel if the number of blocks is predetermined. We then construct a convex optimization problem, which can mimic the original problem structure and permits to jointly consider the power consumption and the probability constraints of the users, to give a suboptimal multiuser time-sharing solution. This is finally combined with the MPE to provide a joint power allocation and time-sharing solution for the time-division multiuser MIMO system. Numerical results demonstrate that the proposed scheme performs nearly the same as the global optimum with inappreciable difference.